Patellar Tendon Reconstruction Using Peroneus Longus Tendon Autograft Following Revision Knee Arthroplasty: A Case Report - Genc, Ahmet Serhat; Guzel, Nizamettin; Arar, Korkut; Agar, Anil (Springernature, 2023)
Patellar tendon rupture is a rare but serious complication resulting in loss of knee extension that may develop during and after total knee arthroplasty and negatively affects the patient's quality of life. There are a number of surgical options available, from primary repair to reconstruction. Peroneus longus tendon autograft has begun to be used for knee extensor mechanism repair in recent years. In this case report, we aimed to present the case of a patient with traumatic patellar tendon rupture after revision knee arthroplasty. In conclusion, patellar tendon reconstruction using peroneus longus tendon autograft can be considered a successful method in selected patients following knee arthroplasty. It allows early rehabilitation via stable graft fixation and provides good clinical and functional outcomes in the late period.
Keywords: knee; autograft; revision arthroplasty; peronous longus; patellar tendon rupture